Pengaruh Teknik Konseling Person Centered Therapy (PCT) terhadap Peningkatan Konsep Diri - Sukur Darman Gulo; Hosianna Rodearni Damanik; Famahato Lase; Justin Foera-era Lase (Counseling Milenial (CM), 2025)
This study aims to determine the extent of the effect of the Person Centered Therapy (PCT) counseling technique on improving students’ self-concept at SMP Negeri 2 Mandrehe. Self-concept is an individual’s idea about themselves, which includes beliefs, perceptions, and evaluations of their own identity. This research employed a quantitative approach. The sampling technique used was probability sampling with a random sampling method. The instruments used in this study were a self-concept questionnaire and a Person Centered Therapy (PCT) questionnaire. The hypothesis testing using simple linear regression with a t-test showed a significance level where the t-value was 1.750 and Sig value was 0.001 < 0.005. This indicates that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. Therefore, it can be concluded that there is a significant effect of the Person Centered Therapy (PCT) counseling technique on improving students’ self-concept at SMP Negeri 2 Mandrehe.